1994
DOI: 10.2136/sssaj1994.03615995005800020026x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Phosphorus Desorption Kinetics and Its Relationship with Plant Growth

Abstract: The kinetics of P desorption in soils is important to consider from a plant nutrition perspective. This study was designed to compare the ability of several equations to describe P desorption kinetics from soils and to relate the information derived from desorption kinetic curves to plant growth and P uptake. Samples of five soils (Psammentic Paleudult, Typic Calciustoll, Udic Pellustert, Vertic Albaqualf, and Aridic Calciustoll) were treated with five P levels (0, 25, 50 75, and 100 mg kg−1) and incubated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…These results agree with those of [25], [26], [28], their results on phosphate showed that both constants were related to the P supplying power of soil and or the rate of P release from soil had significant relationship between β and P bioavailability to sorghum did not establish that P dissolution is a rate determining step to P-uptake since similar relationship existed between β and equilibrium ion.…”
Section: Correlation Analysis Between K Desorption From the Fertilizesupporting
confidence: 88%
See 1 more Smart Citation
“…These results agree with those of [25], [26], [28], their results on phosphate showed that both constants were related to the P supplying power of soil and or the rate of P release from soil had significant relationship between β and P bioavailability to sorghum did not establish that P dissolution is a rate determining step to P-uptake since similar relationship existed between β and equilibrium ion.…”
Section: Correlation Analysis Between K Desorption From the Fertilizesupporting
confidence: 88%
“…The correlation coefficient was highly significant with the kinetic parameters representing the rate of K release in the order: The modified Freundlich rate coefficient (K d ) (r = 0.98**) > the rate constant (β) in the Elovich equation (r = 0.97***) > the rate of K release coefficient (R) in the parabolic diffusion (r = 0.96**) > the initial rate of K-release (q 0 ) in 1 st order equation (r = 0.85**). The β coefficient in Elovich which was found to be inversely correlated with the K supplying power of the soil [ [25][26][27][28][29], and inversely related to the rate of K release from soil [26][27][28][29][30] was inversely correlated with the plant K uptake (r = 0.97 ** ). It should be recalled that both Elovich and modified Freundlich equations offered the best fit to the K release data from the tested adequate fit to the description data, its rate of diffusion coefficient (R) gave the high correlation coefficient with the cumulative K uptake and with the uptake of K. Similarly the first-order equation offered a lower fit to the K release data but the rate constant k 0 of the equation was highly correlated with plant K uptake.…”
Section: Correlation Analysis Between K Desorption From the Fertilizementioning
confidence: 99%
“…Soil P desorption to solution was likely controlled by a combination of Fe (strengite), AL (variscite), and Ca (hydroxyapatite) complexes (McDowell and Sharpley 2003). Also the calcareous soils generally desorbed more P than the acid soils (Raven and Hossner 1994). Crops growing in large region of the world's agricultural soils respond to phosphate fertilization (Bohn et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical methodologies have been tested during the last decades in order to study the available-P status of soils, including chemical extraction (Bowman et al, 1978;Holford, 1980;Matar et al, 1988), anion-exchange resins (Sen Tran et al, 1992;Raven and Hossner, 1994), cationanion-exchange resins (Dalal, 1985;Somasiri and Edwards, 1992), resin membranes (Mallarino and Atia, 2005;Forge et al, 2008;Mason et al, 2008), ferrihydrite-impregnated paper strip (Menon et al, 1989), goethite in dialysis membrane (Delgado, 1996;Delgado and Torrent, 1997), isotopic exchange (Morel and Planchette, 1994;Frossard et al, 1994;Bühler et al, 2003), and electro-ultrafiltration (Simard and Sen Tran, 1993). The main limitation in studying the available-P pool in soils has been the absence of a general method adequate for wide application: depending on the dominant P forms in soils, the relationship between P extracted by plants (available P) and P extracted in the lab is different (Mallarino, 1997).…”
Section: Estimation Of Plant-available P In Soilsmentioning
confidence: 99%